THE IMPACT OF GLOBALIZATION ON CHILD LABOR IN PAKISTAN ANALYZING THE ROLE OF FOREIGN DIRECT INVESTMENT, TRADE LIBERALIZATION, AND SOCIO-CULTURAL FACTORS - Lubna Bibi; Shakir Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
This study examines the complex issue of child labor in Pakistan, focusing on the impact of globalization, specifically through foreign direct investment (FDI) and trade liberalization. These forces have intensified the demand for cheap labor, thereby exacerbating child labor in key sectors such as agriculture, manufacturing, and services. The research explores the traditional socioeconomic structures that sustain child labor and the socio-cultural and economic factors that perpetuate this practice. Utilizing secondary data from academic literature, government reports, and international organizations, the study analyzes how globalization influences child labor in Pakistan. The findings reveal a dual impact of globalization: while it creates economic opportunities, it also leads to increased exploitation of child labor due to weak policy enforcement, poverty, and limited access to education. The study recommends strengthening legal frameworks, enhancing educational opportunities, and implementing social protection programs to mitigate these effects. It also emphasizes the importance of international collaboration and corporate accountability in reducing child labor. A comprehensive approach integrating legal, educational, economic, and social measures is crucial for eradicating child labor and securing a better future for Pakistan's children.